OBSERVATION OF ASTEROID OCCULTATIONS WITH HELP OF THE METHOD OF TEMPORAL UNSQUEEZING CCD-IMAGES IN 2006 - Kravtsov, F. I.; Lukyanyk, I. V. (Одеські астрономічні публікації, 2017)
Description of the method of temporal unsqueezing CCD-images is presented for observations of asteroids occultations. The method was applied for observations of 9 asteroid occultations with telescope AZT - 8 (D = 0.7m, F = 2.8m) and CCD ST - 8MXE in Lisnyky observational station in 2006 year. In really distance between the centers of asteroid and star and time of asteroid occultation only for occultation star TYC 0587-00209-111 by asteroid 76 Freia are obtained on November 4, 2006. For other the minimal distances between the centers of asteroids and stars are determinated. The method lets to observe the asteroid occultations with high time resolution. Distances between the centers of asteroids and stars are obtained with high accuracy.